A2.11 LASP-1 deficiency is changing synovial fibroblast interaction with cartilage matrix in TNFα mediated arthritis. (13th February 2015) - Beckmann, D; Hillen, J; Heitzmann, M; Hansen, U; Chew, CS; Butz, S; Vestweber, D; Pavenstädt, H; Galla, HJ; Pap, T; Korb-Pap, A
Abstract : Background and objectives: Lasp-1 (LIM-and-SH3-domain-protein-1) is an actin-binding protein that modifies cytoskeleton organisation and is localised at cell-matrix interaction sites where it is involved in cell adhesion, migration and metastatic invasion. Its role in regulating synovial fibroblast (SF) interaction with components of extracellular matrix (ECM) and cell-cell contacts during RA is unknown. Furthermore, involved signalling pathways have to be elucidated. Materials and methods: Lasp-1 expression in RA tissue and hind paws of arthritic hTNFtg mice was analysed via Western blot and immunohistochemistry. Furthermore, Lasp-1 ko mice were interbred with hTNFtg mice and offsprings were analysed for the progression of joint destruction by clinical evaluation and histopathology. Cell migration properties of SF derived from wild type (wt), Lasp-1 -/-, hTNFtg and Lasp1 -/- /hTNFtg mice were measured using a modified scratch assay and by live cell imaging. Extracellular matrix structure and organisation from wt, Lasp-1 -/-, hTNFtg and Lasp-1 -/- /hTNFtg SF were analysed by electron microscopy (EM). Cell-matrix interactions as well as cell-cell contacts of isolated SF from mice of all genotypes were investigated using fibronectin and self-purified collagen matrix in an electrical cell/substrate impedance sensing assay (ECIS). Via pull down assays and EM components of integrin mediated cell-matrix interaction complexes were examined. In addition, src-phosphorylation levels were evaluated by Western blot. Results: Lasp-1 expression levels were increased in human RA and in hTNFtg mice compared to healthy controls. Lasp-1 -/- /hTNFtg mice displayed milder clinical symptoms confirmed by immunohistochemistry. Migration assays presented a significantly reduced migration rate of Lasp-1 -/- and Lasp-1 -/- /hTNFtg SF compared to SF from wt and hTNFtg mice. Analyses of SF ECM showed thickened collagen fibrils with less crosslinking of Lasp-1 -/- SF in comparison to wt controls. In ECIS, Lasp-1 -/- SF adhered to both fibronectin and self purified ECM faster than other genotypes (-50% vs. hTNFtg and wt SF). Additionally, Lasp-1 -/- SF formed a higher number of cell-cell contacts than wt and hTNFtg SF (-17% vs. hTNFtg and -22% wt vs. SF). Pull down assays identified cortactin, uPar and vinculin as components of cell-matrix interaction complexes with increased levels of vinculin found in complexes from Lasp-1 -/- compared to wtSF. Finally, both Lasp-1 -/- and Lasp-1 -/- /hTNFtg SF showed reduced src-phosphorylation compared to wt and hTNFtg SF. Conclusion: The loss of Lasp-1 leads to altered src-phosphorylation and changes in cell-matrix interaction complexes as well as altered extracellular matrix organisation. Furthermore, Lasp-1 deficiency leads to significantly reduced migration rates of RASF and hTNFtg SF in vitro and to decreased cartilage degradation in hTNFtg mice in vivo .